Optimalisasi Manajemen Pencegahan Dan Penanggulangan Kebakaran Di Kota Bandung - Setiawan, Wawan Dharma (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
The performance of the Regional Government of Bandung City in preventing and taking care of fire is still being questioned as it is noted that during the last five years there have been 4 to 6 blazes a day. The author sees that in some aspects the fire service is lacking, such as in the aspects of institutional, funding, mapping, and coordinating. Therefore, the efforts to be done by the institution in change are among others: a) preventing blazes through building inspections, law enforcement, consulting Fire Emergency Plan of planned buildings. b) mapping likely areas in fire, c) building well-trained fire brigade, and d) technical assistance for handing blazes. Whereas. Managerial efforts to be done are: a) designing and implementing a Master Plan of Fire System, and b) resource need analysis.